Contribution of Itraconazole Metabolites to Inhibition of CYP3A4 in vivo - Templeton, Ian (2007)
Itraconazole (ITZ) is metabolized in vitro to three inhibitory metabolites: hydroxy-ITZ (OH-ITZ), keto-ITZ, and N-desalkyl-ITZ (ND-ITZ). The goal of this study was to determine the contribution of these metabolites to drug-drug interactions caused by ITZ. Six healthy volunteers received 100 mg ITZ orally for seven days and pharmacokinetic analysis was conducted at day 1 and day 7 of the study. The extent of CYP3A4 inhibition by ITZ and its metabolites was predicted using this data. ITZ, OH-ITZ, keto-ITZ and ND-ITZ, were detected in plasma samples of all volunteers. A 3.9-fold decrease in the hepatic intrinsic clearance of a CYP3A4 substrate was predicted using the average unbound steady-state concentrations (C(ss,ave,u)) and liver microsomal inhibition constants for ITZ, OH-ITZ, keto-ITZ, and ND-ITZ. Accounting for circulating metabolites of ITZ significantly improved the in vitro to in vivo extrapolation of CYP3A4 inhibition compared to a consideration of ITZ exposure alone.